2017
DOI: 10.1111/tme.12391
|View full text |Cite
|
Sign up to set email alerts
|

Audit of provincial IVIG Request Forms and efficacy documentation in four Ontario tertiary care centres

Abstract: Our audit demonstrates a lack of compliance with IVIG Request Form requirements, a lack of documentation of diagnostic criteria and efficacy, and suggests inappropriate use of IVIG. Current implementation of the form may not be sufficient as a strategy for improving appropriate IVIG use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…In this 10‐year retrospective population‐based study of IVIG use at a tertiary care hospital, we confirm the findings of others who have noted that hematologists and neurologists are among the most frequent prescribers of IVIG . Our ITS analyses suggest that changes in IVIG usage trends at the Ottawa Hospital coincided with the release and implementation of provincial initiatives in 2009 and 2010.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this 10‐year retrospective population‐based study of IVIG use at a tertiary care hospital, we confirm the findings of others who have noted that hematologists and neurologists are among the most frequent prescribers of IVIG . Our ITS analyses suggest that changes in IVIG usage trends at the Ottawa Hospital coincided with the release and implementation of provincial initiatives in 2009 and 2010.…”
Section: Discussionsupporting
confidence: 86%
“…Whereas previous work in Canada has sought to evaluate the indications and appropriateness of use of IVIG, large‐scale hospital‐wide descriptive analysis of temporal trends in IVIG use before and after implementation of utilization control programs are few . A retrospective audit of 2014 IVIG request forms and efficacy documentation in four Ontario tertiary care centers found lack of compliance with request form requirements, suggesting that this policy did not have sufficient teeth to effect relevant change . In the same province, a 6‐year evaluation of changes in IVIG prescribing patterns during a period of national product shortage in Canada found that although the number of patients who received IVIG only decreased, the total amount of IVIG distributed during this time remained unchanged …”
Section: Discussionmentioning
confidence: 99%
“…We do not know the ultimate resolution of reviewed claims-whether denied, appealed, contested, or reversed. The findings by Levine et al parallel a recent Canadian experience by Shih et al 5 from a McMaster University audit. Their chart review of all IVIg uses (178 patients) found that 33% of charts lacked adequate documentation for a confirmable diagnosis, even for Guillain-Barré syndrome in some instances.…”
supporting
confidence: 78%
“…6 The escalating use of IVIG has become a top priority for the transfusion medicine community due to high cost and threatened sustainability. 7,8 A key advantage of rituximab over IVIG is the potential for durable responses. In patients with immune thrombocytopenia (ITP), IVIG results in a rapid but transient platelet (PLT) count improvement in more than 80% of patients, 9 whereas rituximab can induce a PLT count increase in 50% to 60%, and in roughly 25% of patients, that response can be sustained for 18 months or longer.…”
mentioning
confidence: 99%